Potentiation of Gamma Aminobutyric Acid Receptors (GABAAR) by Ethanol: How Are Inhibitory Receptors Affected? - Förstera, Benjamin; Castro, Patricio A.; Moraga-Cid, Gustavo; Aguayo, Luis G. (Frontiers in Cellular Neuroscience, 2016)
In recent years there has been an increase in the understanding of ethanol actions on the type A -aminobutyric acid chloride channel (GABAAR), a member of the pentameric ligand gated ion channels (pLGICs). However, the mechanism by which ethanol potentiates the complex is still not fully understood and a number of publications have shown contradictory results. Thus many questions still remain unresolved requiring further studies for a better comprehension of this effect. The present review concentrates on the involvement of GABAAR in the acute actions of ethanol and specifically focuses on the immediate, direct or indirect, synaptic and extra-synaptic modulatory effects. To elaborate on the immediate, direct modulation of GABAAR by acute ethanol exposure, electrophysiological studies investigating the importance of different subunits, and data from receptor mutants will be examined. We will also discuss the nature of the putative binding sites for ethanol based on structural data obtained from other members of the pLGICs family. Finally, we will briefly highlight the glycine gated chloride channel (GlyR), another member of the pLGIC family, as a suitable target for the development of new pharmacological tools.